Predictive modelling of individual well-being among professional engineers - Norizan Baba Rahim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Engineers have a crucial role in furthering Malaysia’s technological advancements. Besides, engineers are important in creating wealth and they assist the nation in becoming an active player in the global market. They possess special knowledge and expertise and are known to be driven to climb the career ladder. However, sometimes the engineers’ vision, ambition, goals, and expectations do not align with those of their employers. As a result, the conflict between being ambitious and the work demand structured by employers has affected engineers’ well-being (WB). In this study, the effect between protean career orientation (PCO) [self-directed (SD) and valuesdriven (VD)] and individual WB [career satisfaction (CS) and psychological WB (PWB)] was investigated using a sample of 261 male and 126 female professional engineers (PEs) with the mean age of 42 years old. The research model was examined via the protean career theory. Partial least square (PLS) regression findings revealed that PCO (VD) positively influenced CS. Besides, PCO (SD) also positively affected PWB. Based on the findings, this research suggests that organisations perform necessary amendment to the PEs’ key performance areas, for them to know that their goals and expectations are parallel with their employers’. Moreover, employers need to offer opportunities and allow the PEs to maximally utilise their skills or to grow their abilities to full potential. Consequently, PEs will have an increased level of CS and PWB.